ผลของโปรแกรมสุขศึกษาโดยการประยุกต์ใช้แบบแผนความเชื่อสุขภาพในการป้องกันโรคเอดส์ ในนักเรียนชั้นมัธยมศึกษาตอนต้น จังหวัดขอนแก่น - สมมาตย์, เจตนิพิฐ; อุยวัฒนกุล, พิมพ์ศิริ (Ratchaphruek Journal, 2016)
การวิจัยกึ่งทดลองครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาผลของโปรแกรมสุขศึกษาโดยการประยุกต์ใช้แบบแผนความเชื่อสุขภาพในการป้องกันโรคเอดส์ในนักเรียนชั้นมัธยมศึกษาตอนต้น จังหวัดขอนแก่น กลุ่มตัวอย่าง จำนวน 81 คน แยกเป็นกลุ่มทดลอง จำนวน 46 คน กลุ่มเปรียบเทียบ จำนวน 35 คน คัดเลือกโดยวิธีการสุ่มแบบอย่างง่าย กลุ่มทดลองได้รับโปรแกรมสุขศึกษาที่ประยุกต์จากแนวคิดแบบแผนความเชื่อสุขภาพเป็นระยะเวลา 4 สัปดาห์ กิจกรรมประกอบด้วยการบรรยาย การฉายวีดีทัศน์ การแลกเปลี่ยนความคิดเห็น การวิเคราะห์กรณีศึกษา การเล่นเกม การสาธิตและการฝึกปฏิบัติ รวบรวมข้อมูลก่อนและหลังการทดลอง โดยใช้แบบสอบถาม วิเคราะห์ข้อมูลเพื่อเปรียบเทียบคะแนนเฉลี่ยภายในกลุ่มด้วย Paired t-test และ Wilcoxon signed-rank test เปรียบเทียบคะแนนเฉลี่ยระหว่างกลุ่มด้วย Independent t-test และ Wilcoxon rank-sum (Mann-Whitney) test กำหนดระดับนัยสำคัญที่ .05 ผลการศึกษาพบว่า หลังการทดลอง กลุ่มทดลองมีคะแนนเฉลี่ยการรับรู้ต่อโอกาสเสี่ยงของการติดเชื้อเอดส์ และการรับรู้อุปสรรคของการป้องกันโรคเอดส์สูงกว่าก่อนการทดลอง และกลุ่มเปรียบเทียบอย่างมีนัยสำคัญทางสถิติ (P<0.0001) ยกเว้นการรับรู้ความรุนแรงของโรคและการรับรู้ประโยชน์ของการป้องกันโรคเอดส์ Effects of Health Education Program Using Health Belief Model for AIDS Prevention among Junior High School Students in Khon Kaen Province This quasi-experimental research aimed to assess the effects of health education program using health belief model for AIDS prevention among junior high school students in Khon Kaen. Participants were 81 students who were recruited by using simple random sampling and assigned 46 students into an experimental group and 35 students into a comparison group. The experimental group participated in the health education program based on health belief model for four weeks. The main activities were lecture, video tape projection, group discussion, opinion sharing, case study, games, demonstration and practice. Data were collected using selfadministered questionnaire before and after the intervention program and were analyzed by using paired t-test, Wilcoxon signed-rank test to compare the means differences within group and independent t-test, Wilcoxon rank-sum (Mann-Whitney) test to compare the means differences between groups at the 0.05 level of significance. The results after the intervention of the experimental group showed that it had significantly higher means of perceived AIDS susceptibility, and perceived barriers of AIDS prevention than before the intervention and higher than the comparison group with statistical significance (P<0.0001), except perceived AIDS severity and perceived benefits of AIDS prevention.